DIGITISASI SEBAGAI UPAYA PRESERVASI ARSIP FOTO DPRD KABUPATEN BANDUNG DI DINAS PERPUSTAKAAN DAN ARSIP KABUPATEN BANDUNG - Nida Hanifah; Mas Dadang Enjat Munajat; Wawat Setiawati (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2026)
Archive digitization is the activity of converting archives from analog or physical form into digital form archives and it becomes a strategic effort to support preservation. This research is important because the Bandung Regency DPRD’s photo archives hold significant historical value as part of the region’s collective memory, yet they are vulnerable to physical damage and loss of information over time. Furthermore, this research is expected to contribute to the development of digital archival studies, particularly by providing an overview of the implementation of photo archive digitization as a preservation effort in regional archival institutions. The purpose of this research is to find out about digitization as an effort to preserve the DPRD Kabupaten Bandung photo archives. This research is a type of qualitative research. The data in this study were obtained through observation, interviews, and documentation. The results of this study reveal that there are shortcomings in each important stage of digitization as an effort to preserve the DPRD Kabupaten Bandung photo archives, namely selection, information capture, processing, archiving, and presentation, but it is still an important step as an effort to preserve the DPRD Kabupaten Bandung photo archives, which has historical value. Keywords: digital archives; digitalization; digitization; curratiom; preservation; photo archives